2012
DOI: 10.1590/s1984-82502012000400019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of whey protein hydrolysates: peptide profile and ACE inhibitory activity

Abstract: The aim of this study was to prepare enzymatic hydrolysates from whey protein concentrate with a nutritionally adequate peptide profile and the ability to inhibit angiotensin-converting enzyme (ACE) activity. The effects of the type of enzyme used (pancreatin or papain), the enzyme:substrate ratio (E:S ratio=0.5:100, 1:100, 2:100 and 3:100) and the use of ultrafiltration (UF) were investigated. The fractionation of peptides was performed by size-exclusion-HPLC, and the quantification of the components of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
3
15
1
4
Order By: Relevance
“…At higher DH, a higher ACE inhibitory bioactivity was achieved. This result is in line with the work reported by Silvestre et al [36] and Ghanbari et al [37], in which the ACE-inhibitory activity of protein hydrolysates was affected by the type of enzymes as well as the degree of hydrolysis. Also, the increased level of E/S ratio and alkali pH resulted in high values of DH to indicate the release of potent peptides which further contributed towards the strong ACE-inhibitory activity.…”
Section: Ace-inhibitory Activitysupporting
confidence: 93%
“…At higher DH, a higher ACE inhibitory bioactivity was achieved. This result is in line with the work reported by Silvestre et al [36] and Ghanbari et al [37], in which the ACE-inhibitory activity of protein hydrolysates was affected by the type of enzymes as well as the degree of hydrolysis. Also, the increased level of E/S ratio and alkali pH resulted in high values of DH to indicate the release of potent peptides which further contributed towards the strong ACE-inhibitory activity.…”
Section: Ace-inhibitory Activitysupporting
confidence: 93%
“…From a structure activity point of view of ACE inhibitors, studies have demonstrated that the ACE inhibitory activity of a peptide depends on the presence of specific residues at N and C-termini [8]. The presence of hydrophobic residues, particularly leucine, valine, isoleucine, and glycine, at the N-terminus of a peptide, produced higher ACE inhibitory activity, while aromatic amino acids, such as phenylalanine, proline, tryptophan, and tyrosine, are preferred at the C-terminus [55]. Additionally, the presence of positively charged residues, specifically arginine and lysine, near the C-terminus were also considered to be essential for the ACE inhibitory potential of peptides [56].…”
Section: Discussionmentioning
confidence: 99%
“…Hayes et al [6] have shown that after fractionation, the 3-kDa boarfish protein hydrolysate generated using protease AP inhibited the ACE by 85.8 % at 1 mg/ml, while the hydrolysate showed an activity of 72.08%. On the other hand, Silvestre et al [11] have reported that the UF process may cause the retention of peptides with structures (aromatic amino acids or proline at the C-terminal position) that favor ACE-inhibitory activity. However, in some cases, UF showed no effect on the enhancement of the ACE-inhibitory activity.…”
Section: Evaluation Of the Ace-inhibitory Activitymentioning
confidence: 99%